State of knowledge of research on the teaching-learning process of foreign languages in Colombia (2011-2021) (Revista Investigium IRE Ciencias Sociales y Humanas, 2023)
Foreign language teaching in Colombia has received attention over the past 15 years. Such attention has materialized in government investment and research by the academic community. However, further analysis is required so that the academic community of Foreign Languages can make informed decisions and guide efforts to improve the quality of language teaching in the country. This paper reviews the literature on the teaching and learning processes of foreign languages from 2011 to 2021. The purpose of the study is to identify theoretical and methodological trends and potential areas for development. Thus, the PRISMA guidelines were used for systematic reviews and meta-analyses. After applying inclusion, exclusion and thematic relevance criteria in Scopus, WoS (Web of Science), Publindex and Google Scholar, a sample of 129 studies was formed. The selected studies show trends in terms of language, region of publication, research methods, and topics. Our conclusions indicate that foreign language research in Colombia is mainly related to the teaching of English. There is a clear preference for qualitative methodologies and a predominant focus of research on technology and its associated topics. Finally, there is a marked disparity in regional research outcomes, revealing systemic inequalities in the opportunities and resources available for academic research and highlighting the urgency of channeling efforts to improve underrepresented regions, ensuring that all areas of Colombia have an equitable position in the global academic context.